2010
DOI: 10.1021/ja103655f
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Shapes of Silver Nanocrystals with Different Capping Agents

Abstract: This paper provides direct evidence to support the role of a capping agent in controlling the evolution of Ag seeds into nanocrystals with different shapes. Starting with single-crystal seeds (spherical or cubic in shape), we could selectively obtain Ag octahedrons enclosed by {111} facets and nanocubes/nanobars enclosed by {100} facets by adding sodium citrate (Na(3)CA) and poly(vinyl pyrrolidone) (PVP), respectively, as a capping agent while all other parameters were kept the same. This research not only off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
371
1
12

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 427 publications
(395 citation statements)
references
References 25 publications
11
371
1
12
Order By: Relevance
“…To date, CAs have played an important role on shape‐controlled synthesis of NCs,137, 138, 139, 140, 141, 142 and there are many successful examples in preparing Cu 2 O NCs 7, 8, 75, 107, 122, 125, 143. We will introduce some classic synthetic routes of Cu 2 O NCs enclosed by low‐index facets.…”
Section: Basic Growth Strategies For Cu2o Polyhedramentioning
confidence: 99%
“…To date, CAs have played an important role on shape‐controlled synthesis of NCs,137, 138, 139, 140, 141, 142 and there are many successful examples in preparing Cu 2 O NCs 7, 8, 75, 107, 122, 125, 143. We will introduce some classic synthetic routes of Cu 2 O NCs enclosed by low‐index facets.…”
Section: Basic Growth Strategies For Cu2o Polyhedramentioning
confidence: 99%
“…On the other hand, from the viewpoint of nanofabrication, it has been demonstrated that the size of the produced nanostructures in a colloid system could be decreased by introducing polymeric surfactant molecules to the synthesis system [30,[34][35][36][37][38][39][40]. These polymeric surfactant molecules are suggested to work as stabilizer or capping agents to hamper the further growth of the formed nanospecies, resulting in smaller nanostructures [30,[34][35][36][37][38][39][40]. For example, it has recently been reported that the size of the Ag/AgCl nanoparticles could be decreased with the assistance of polymeric surfactant molecules, poly(vinyl pyrrolidone) [40].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
“…For example, it has recently been reported that the size of the Ag/AgCl nanoparticles could be decreased with the assistance of polymeric surfactant molecules, poly(vinyl pyrrolidone) [40]. On the basis of these well-documented understandings [30,[32][33][34][35][36][37][38][39][40] and accompanied by our experimental facts, we suggest that in our system the GO nanosheet, an unconventional amphiphilic polymer, might work as capping agent or stabilizer to hamper the further growth of the Ag/Ag 3 PO 4 nanoparticles, resulting in smaller size of the formed nanostructures. Similar results have been reported in other systems [28][29][30].…”
Section: Synthesis and Characterization Of Ag/ag 3 Po 4 And Go Hybridmentioning
confidence: 99%
“…it can act as a reducing reagent and/or as a capping agent [20][21][22][23]. This capping agent provides the nanoparticles with sufficient electrostatic stabilization to avoid agglomeration for long periods of time.…”
Section: Introductionmentioning
confidence: 99%